2012
DOI: 10.4067/s0717-95022012000200034
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Group Exercise Program on Muscular Function among Fall-Prone Elderly Women

Abstract: SUMMARY:In a sampled population of fall-prone elderly women, an exercise protocol was performed for 12 weeks on experimental group and at the end of exercise period, the strength and endurance of muscles and SF-6 Health Surveys were analyzed. Results showed that endurance and strength of muscles and also physical activity were improved in experimental group (P<0.05). Group exercise program causes improvement in both strength and endurance of muscles in fall-prone elderly women. The effect of group exercise pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Behpor et al, reported that a 12-week group exercise program improved the endurance and muscle strength of fall-prone elderly women. 34 The same results in Behpor and the present study may be related to doing group physical activities and creating a motivational and invigorating environment. Mathieu L. Maltais also found that resistance training is an effective way to increase muscle mass and strength.…”
Section: Discussionsupporting
confidence: 82%
“…Behpor et al, reported that a 12-week group exercise program improved the endurance and muscle strength of fall-prone elderly women. 34 The same results in Behpor and the present study may be related to doing group physical activities and creating a motivational and invigorating environment. Mathieu L. Maltais also found that resistance training is an effective way to increase muscle mass and strength.…”
Section: Discussionsupporting
confidence: 82%